Aging and the future ahead - Mohammad Rahmani Zarvandi (Shahid Beheshti University of Medical Sciences, 2018)
For downloading the full-text of this article please click here. The population of the elderly in Iran already is 8 million and is rapidly increasing. Aging is a phenomenon with cultural, social, political, economic and religious dimensions. This phenomenon can be studied from various viewpoints, some of which are discussed here.For downloading the full-text of this article please click here.